Assessment of the physiological potential of spinach seeds (Tetragonia tetragonoides (Pall.) Kuntze) - Lodo, Maria Angélica [UNESP]; Lopes, Magnólia De Mendonça [UNESP]; Soares, Bruna Resende Ribeiro [UNESP]; Vieira, Roberval Daiton (Associação Brasileira de Tecnologia de Sementes (ABRATES), 2013)
The efficiency of vigor tests in assessing the physiological potential of seeds depends on their standardization for different species. In this context, the research aimed to study specific methodologies to evaluate the vigor of spinach seeds (Tetragonia tetragonoides). For this purpose, five lots of spinach seed cv. New Zealand were submitted to germination, first count of germination, seedling emergence in the field, accelerated aging (with and without use of saturated solution of NaCl at 41and 45 ºC for 24,48 and 72 hours), controlled deterioration (18,21 and 24% seed water content adjustments for 24 hours at 45 ºC) and electrical conductivity tests with variations inwater volume (25, 50 and 75 mL), seed quantity (25 and 50) and soaking period (1, 2, 4, 8,12, 16 and 24 hours) at 25 ºC. The first count test allowed obtaining preliminary information about seed vigor, and other tests in general showed similarity with seedling emergence in the field. Thus, it was concluded that traditional accelerated aging test 24 h /41 ºC and accelerated aging test with saturated salt solution for 24 h at 41 ºC and 45 ºC, and controlled deterioration test with 21% seed water content / 24 h / 45 ºC were all efficient for evaluating the physiological potential of spinach seeds.

A eficiência dos testes de vigor na avaliação do potencial fisiológico de sementes depende do desenvolvimento e/ou do ajuste de metodologias para as diferentes espécies. Nesse contexto, o objetivo da pesquisa foi adequar procedimentos para avaliação do potencial fisiológico de sementes de espinafre. Para tanto, sementes de cinco lotes, da cultivar Nova Zelândia, foram submetidas aos testes de germinação, primeira contagem da germinação, emergência de plântulas, envelhecimento acelerado (com e sem o uso de solução saturada de NaCl a 41 e 45 ºC por 24, 48 e 72 h), deterioração controlada (18, 21 e 24% de teor de água por 24 h a 45 ºC) e condutividade elétrica (25 e 50 sementes, 25, 50 e 75 mL de água de embebição por 1, 2, 4, 8, 12, 16 e 24 h, a 25 ºC). Pode-se concluir que os testes de envelhecimento acelerado tradicional 24 h / 41º C, envelhecimento acelerado com solução salina por 24 h a 41 e 45 °C e deterioração controlada a 21% / 24 h a 45 °C foram eficientes para avaliar o potencial fisiológico e para classificar os lotes de sementes de espinafre em níveis de vigor.
Avaliação do potencial fisiológico de sementes de espinafre (Tetragonia tetragonoides (Pall.) Kuntze)
Keywords: vegetable crop; adaptation of procedures; Vigor; hortaliça; adequação de procedimentos; Vigor